Identification of Writing Skills in Hamzah Script by PBA Students UIN North Sumatra Students - Andika, Arya; Aditya, Muhammad Zaki; Nasution, Sahkholid (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
This study aims to identify the ability of writing hamzah in students of the Arabic Language Education Study Program (PBA) at UIN Sumatera Utara. This study uses a qualitative method with data collection techniques in the form of library research and questionnaires. The sample of this study is 5 alumni of PBA UIN SU students who were selected purposively. The data obtained were then analyzed using descriptive qualitative analysis. The results of this study show that the ability of writing hamzah in PBA UIN SU students is very good, with an average score of 100. The factors that support the high ability of writing hamzah include mastery of the theory and rules of writing hamzah, practice and habituation of writing Arabic words that contain hamzah, and attention and motivation in learning to write hamzah. This study recommends the need for the application of qualitative methods in learning to write hamzah in PBA UIN SU, as well as the development of library research and questionnaires as assessment instruments.